Developmental programming in human umbilical cord vein endothelial cells following fetal growth restriction - Terstappen, Fieke (Clin Epigenetics, 2020)
BACKGROUND: Fetal growth restriction (FGR) is associated with an increased susceptibility for various noncommunicable diseases in adulthood, including cardiovascular and renal disease. During FGR, reduced uteroplacental blood flow, oxygen and nutrient supply to the fetus are hypothesized to detrimentally influence cardiovascular and renal programming. This study examined whether developmental programming profiles, especially related to the cardiovascular and renal system, differ in human umbilical vein endothelial cells (HUVECs) collected from pregnancies complicated by placental insufficiency-induced FGR compared to normal growth pregnancies. Our approach, involving transcriptomic profiling by RNA-sequencing and gene set enrichment analysis focused on cardiovascular and renal gene sets and targeted DNA methylation assays, contributes to the identification of targets underlying long-term cardiovascular and renal diseases. RESULTS: Gene set enrichment analysis showed several downregulated gene sets, most of them involved in immune or inflammatory pathways or cell cycle pathways. seven of the 22 significantly upregulated gene sets related to kidney development and four gene sets involved with cardiovascular health and function were downregulated in FGR (n = 11) versus control (n = 8). Transcriptomic profiling by RNA-sequencing revealed downregulated expression of LGALS1, FPR3 and NRM and upregulation of lincRNA RP5-855F14.1 in FGR compared to controls. DNA methylation was similar for LGALS1 between study groups, but relative hypomethylation of FPR3 and hypermethylation of NRM were present in FGR, especially in male offspring. Absolute differences in methylation were, however, small. CONCLUSION: This study showed upregulation of gene sets related to renal development in HUVECs collected from pregnancies complicated by FGR compared to control donors. The differentially expressed gene sets related to cardiovascular function and health might be in line with the downregulated expression of NRM and upregulated expression of lincRNA RP5-855F14.1 in FGR samples; NRM is involved in cardiac remodeling, and lincRNAs are correlated with cardiovascular diseases. Future studies should elucidate whether the downregulated LGALS1 and FPR3 expressions in FGR are angiogenesis-modulating regulators leading to placental insufficiency-induced FGR or whether the expression of these genes can be used as a biomarker for increased cardiovascular risk. Altered DNA methylation might partly underlie FPR3 and NRM differential gene expression differences in a sex-dependent manner.